Of scales, networks and assemblages: the League of Nations apparatus and the scalar sovereignty of the Government of India - Legg, Stephen (Wiley, 2009)
Whilst greatly valuing recent critiques of the vertical imaginary and reified ontology of scale theory, and of the unfettered flows of network theory, this paper argues against a human geography without scale. Rather, four propositions from the theoretical literature are used to provide a tool-kit to analyse the practical negotiation of scalar politics, namely that: scales should be considered as effects, not frames or structures, of practice; networks must be considered in all their complexity and heterogeneity; networks can be interpreted as assemblages, the more re-territorialising and re-scaling of which can be analysed as apparatuses; and that state apparatuses work to create the impression that scales are ahistorical, hierarchical and possess exclusive relationships. These propositions are used to explore a period of history when the scalar constitution of the world was under intense debate. The interwar era saw the imperial scale clash with that of the international, both as ideological worldviews, and as a series of interacting institutions. The assemblages of internationalism and imperialism were embodied by apparatuses such as the League of Nations and the colonial Government of India respectively. Attempts by the League to encourage the abolition of tolerated brothels in an attempt to reduce the trafficking of women and children led to intense debates between the 1920s and 1930s over what constituted the legitimate domains of the international and the ‘domestic’. These explicitly scalar debates were the product of League networks that threatened the scalar sovereignty of the Raj, most directly through the travelling Commission of Enquiry into Traffic in Women and Children in the East in 1931.